Ag/polydopamine-coated textile for enhanced liquid/liquid mixtures separation and dye removal - Gan Miao; Fangchao Li; Zhongshuai Gao; Ting Xu; Xiao Miao; Guina Ren; Yuanming Song; Xiangming Li; Xiaotao Zhu (iScience, 2022)
Summary: Engineering a versatile platform that enables to separate both oil/water and oil/oil mixtures and remove dye from water is not easy. To address this challenge, we have developed an Ag/polydopamine-coated textile (Ag/PDA@textile) by chemically depositing Ag particles on the textile surface using polydopamine as the binder layer. The obtained Ag/PDA@textile attracts water but repels oil in the air, underwater, and when immersed into the oil. Exploiting its water-attracting and oil resistance, the Ag/PDA@textile is acted as a separation membrane to separate oil/water mixtures with enhanced separation efficiency. The Ag/PDA@textile also possesses opposite wetting behavior to oils with different polarities, allowing it to separate oil/oil mixtures efficiently. Thanks to the catalytic performance of the Ag particle, organic dyes can be decomposed effectively by our Ag/PDA@textile under UV illustration or in the presence of NaBH4. Our Ag/PDA@textile may be valuable for applications in water purification and oil sewage treatment.